OpenSky Report 2024: Analysis of Global Flight Contrail Formation and Mitigation Potential - Sun, Junzi; Olive, Xavier; Roosenbrand, Esther; Parzani, Celine; Strohmeier, Martin (IEEE/AIAA Digital Avionics Systems Conference, 2024)
With the increasing coverage of the OpenSky, flight data gathered from the network of receivers has become a primary source of open data for aviation research. This year marks ten years of OpenSky. In this report, we employ a year's worth of OpenSky data to analyze the formation of contrails and study the potential mitigation with altitude diversions. Persistent contrails, often formed under humid atmospheric conditions, significantly trap outgoing terrestrial radiation. More insights into contrails are essential for studying aviation climate impact. We estimated the potential formation of persistent contrails based on the numerical weather assimilation data. An efficient approach is employed to fuse meteorology data in our analysis, which allows the fast evaluation of these contrail conditions at a very large scale. We designed a simple yet effective algorithm for flight with persistent contrails to study the shortest altitude diversion that would have prevented the contrail formations. We have estimated that between 5 % and 9 % of total flight distances each month could have formed persistent contrails. Furthermore, altitude diversions could have mitigated 70 % of these contrails.